Initial Results of D3 Lymphadenectomy in the Surgical Treatment of Cancer of the Right Half of the Segmented Intestine - R. T. Aiypov; R. I. Safiullin; M. R. Garipov; D. V. Feoktistov; N. A. Tarasov; A. A. Garipova; R. R. Garipov (Креативная хирургия и онкология, 2018)
Introduction. Despite recent significant progress in chemotherapy treatment of primary non-metastatic cancer of the right half of the segmented intestine, surgery remains the primary method of treatment. Radical surgery includes removal of the tumour within the healthy tissues and regional lymph glands. Considering localisation of the primary tumour in the right half of the segmented intestine, hemicolectomy is typically performed on the right side. W. Hohenberger et al. have formulated a new concept of radical surgical treatment of the segmented intestine, consisting of the following components: complete mesocolic excision, early ligation of the lymphovascular pedicle and lymph dissection in the D3 volume.Purpose of the research: to analyse the early results of surgical treatment of cancer in the right half of the segmented intestine in the volume of the right-side hemicolectomy with D3 lymph node dissection depending on the method of surgical treatment.Materials and methods. At the premises of the Surgical Department No. 3 of the Republican Oncologic Dispensary (city of Ufa) a retrospective analysis of data of 59 patients was performed following right-side hemicolectomy using complete mesocolic excision, ligation lymphovascular pedicles and lymph node dissection in the D3 volume. Depending on the surgical access, all patients were divided into two main groups: group I (48 patients) — surgeries were performed using open method; group II (11 patients) — using laparoscopy.Results and discussion. Table 2 shows that the surgery performed with laparoscopy takes longer. However, statistically it results in significantly less blood loss. Patients who underwent open surgery were characterised by a longer stay in hospital. One of the effectiveness criteria is the number of removed lymph glands not differing for either group.Conclusion. Extended lymph dissection in the D3 volume for segmented intestine on the right side during cancer is a possible and safe method in case of laparoscopic and open procedures.